A COMPREHENSIVE REVIEW: DYSREGULATION OF GLUCOSE METABOLISM IN PREGNANCY AND INNOVATIVE STRATEGIES FOR PREVENTION-FOCUSED MIDWIFERY CARE: Tinjauan Komprehensif: Disregulasi Metabolisme Glukosa pada Kehamilan dan Strategi untuk Asuhan Kebidanan Preventif - sofiyanti, santi (Jurnal Kesehatan Siliwangi, 2025)
Pregnancy triggers complex metabolic changes, particularly in glucose homeostasis. This vital adaptation, marked by physiological insulin resistance in the second and third trimesters, ensures an adequate glucose supply for the fetus. However, a failure of pancreatic beta-cell compensation can lead to Gestational Diabetes Mellitus (GDM), a significant obstetric complication. GDM shares pathophysiological similarities with type 2 diabetes (T2D) and poses substantial risks, including adverse perinatal outcomes (e.g., macrosomia and preeclampsia) and long-term consequences such as increased maternal T2D risk and offspring susceptibility to obesity via fetal programming. Despite these known impacts, GDM diagnosis remains challenging due to a lack of uniform diagnostic standards and often-delayed screening. This review, therefore, aims to comprehensively examine the physiological adaptations, factors influencing glucose dysregulation, and clinical implications of GDM. Furthermore, it evaluates current management strategies and identifies future research directions, emphasizing the crucial role of midwives in developing innovative, prevention-based approaches from preconception through the breastfeeding period to improve overall maternal and child health. Key words: Gestational Diabetes, Glucose Metabolism, Midwife, Prevention